Legal Protection in Fulfilling the Right to Employment for Persons with Disabilities - Tahta Rifatul Ulya; Zuiyin Zuhda Nailarruhma; Alya Alfa Adilia; Ahmad Azza El-Fadholy (Disable, 2025)
This study explores the gap between normative legal protection and the actual implementation of employment rights for persons with disabilities in Indonesia’s Civil Servant (ASN) recruitment. Although affirmative action policies mandate a minimum quota of 2%, representation remains far below the threshold. The core issue lies in inconsistencies between legal norms and technical practices, especially administrative and medical requirements that often prove discriminatory. Using a normative legal method with statutory and conceptual approaches, the research draws on laws and regulations concerning disability and civil service, alongside scholarly literature. Analysis employs systematic, grammatical, and teleological interpretation. Findings reveal ineffective implementation due to regulatory disharmony, restrictive medical standards, lack of reasonable accommodation, and weak oversight, all of which create structural barriers to equal access. This study contributes by linking legal protection frameworks with recruitment mechanisms—an area rarely examined—and proposes reforms including regulatory harmonization, a shift from medical to functional assessment, and stronger supervisory institutions. These measures are essential to ensure substantive equality and uphold employment rights for persons with disabilities in civil service recruitment.